2021
DOI: 10.1038/s41467-021-23686-9
|View full text |Cite
|
Sign up to set email alerts
|

The archaeal protein SepF is essential for cell division in Haloferax volcanii

Abstract: In most bacteria, cell division depends on the tubulin homolog FtsZ and other proteins, such as SepF, that form a complex termed the divisome. Cell division also depends on FtsZ in many archaea, but other components of the divisome are unknown. Here, we demonstrate that a SepF homolog plays important roles in cell division in Haloferax volcanii, a halophilic archaeon that is known to have two FtsZ homologs with slightly different functions (FtsZ1 and FtsZ2). SepF co-localizes with both FtsZ1 and FtsZ2 at midce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 64 publications
0
38
0
Order By: Relevance
“…The Z–ring is anchored to the membrane with the help of other essential cell division proteins, such as FtsA and ZipA of E. coli ( Pichoff and Lutkenhaus, 2002 ). In Gram positive bacteria as well as FtsZ-containing archaea, SepF is the key membrane anchor for FtsZ ( Duman et al, 2013 ; Nussbaum et al, 2021 ; White and Eswara, 2021 ).…”
Section: Overall Ftsz Structure and Functionmentioning
confidence: 99%
“…The Z–ring is anchored to the membrane with the help of other essential cell division proteins, such as FtsA and ZipA of E. coli ( Pichoff and Lutkenhaus, 2002 ). In Gram positive bacteria as well as FtsZ-containing archaea, SepF is the key membrane anchor for FtsZ ( Duman et al, 2013 ; Nussbaum et al, 2021 ; White and Eswara, 2021 ).…”
Section: Overall Ftsz Structure and Functionmentioning
confidence: 99%
“…Recent data has added further information on the FtsZ-based cell division machinery in archaea by showing for the first time that a homologue of SepF anchors the Z-ring to the membrane, as it does in many bacteria 102 , 103 ( Figure 4F ). Interestingly, however, the structure of SepF in complex with FtsZ show striking differences from its bacterial counterpart; this may reflect the early evolutionary divergence of the cell envelopes in the two prokaryotic domains and/or differences in SepF/FtsZ function required to deform such very different types of cell walls 102 , 103 . Curiously, and differently from bacteria, none of the MinD homologues identified in H. volcanii are involved in localizing FtsZ at midcell 104 .…”
Section: Introductionmentioning
confidence: 97%
“…The function of SepF in cell division was first discovered in Streptococcus pneumonia , that the depletion of SepF leads to highly deformed septa . Similarly, the depletion of SepF in Haloferax volcanii or Mycobacterium tuberculosis results in the formation of large cells or defective growth. Further studies indicated an additional function of SepF in Bacillus subtilis to shape the cell wall due to its intrinsic property of forming ring structures .…”
Section: Introductionmentioning
confidence: 99%
“…SepF is located at the Z-ring forming area and has a direct interaction with FtsZ during division. It interacts with the C-terminus of FtsZ like many other regulating proteins and is a candidate for FtsZ membrane tethering. In SepF-deleted cells, FtsZ failed to localize to the site of division. , Meanwhile, copolymerization of FtsZ and SepF in vitro lead to a promotion of the assembly and protofilament bundling of FtsZ . The action mode between SepF and FtsZ has been suggested by crystal structures obtained from bacteria Corynebacterium glutamicum and archaea Methanobrevibacter smithii .…”
Section: Introductionmentioning
confidence: 99%